The influence of corporate governance and human governance towards corporate financial crime in Malaysia / Wan Nailah Abdullah - Abdullah, Wan Nailah (Institute of Graduate Studies, UiTM, 2018)
Corporate financial crime (CFC) incidences happen every single year in listed companies of Bursa Malaysia, regardless of various recognitions received for exemplary practices of corporate governance (CG) standard. CFC involving listed companies can be traced down through the Securities Commission's criminal cases and various reports in the mass-media. The ineffectiveness of CG mechanisms in curbing this crime has been proposed in this study as being due to the inappropriateness of CG as —corporate mechanisms• to be used as means for controlling the behaviour of human-being behind the organization. The study, hence, proposes the significance of human governance (HG) factors to be explored, in investigating their effectiveness in mitigating CFC. HG has been used to address the issue of CG's failure as a controlling mechanism, suggesting that there should be needs to concentrate on people, as in the study i.e., directors and top management teams, in formulating the governance regulations. Motivated by lack of studies in CFC in Malaysia and empirical evidence in the area of HG, the study is significance to the literature through the inclusion of HG factors in the area of CFC. Using educational background and previous job experiences of directors and top management teams (TMT) as proxies to HG, the study postulates that organizations with higher HG are expected to be free from CFC incidences. In addition, the study also seeks to investigate the effectiveness of internal and external governance in relation to CFC incidences to find out whether CG roles are still relevantly effective in the current situation…